2022
DOI: 10.1149/1945-7111/ac63f4
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Transmission Electron Microscopy Study of Shrinkage Kinetics of CH4N-Molecular-Ion-Implantation-Induced Extended Defects

Abstract: The thermal stability of end-of-range (EOR) defects formed in a CH4N-molecular-ion-implanted epitaxial silicon (Si) wafer was studied by transmission electron microscopy (TEM). We found that the density and size of the CH4N-ion-implantation-induced EOR defects negligibly changed upon heat treatment at temperatures below 1000ºC, whereas the EOR defect density was drastically reduced by heating at 1100ºC. Additionally, in situ cross-sectional TEM observation during heat treatment showed that the EOR defects grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previously, we have clarified the thermal stability and shrinkage behavior of FDLs formed in CH 4 N-multielement-molecular-ion-implanted epitaxial Si wafer. 35 We found that the faulted Frank dislocation loops (FDLs) formed in a CH 4 N-ion-implanted epitaxial Si wafer are thermally stable up to 1000 °C, and at temperatures above 1100 °C, most of them lose stability and finally dissolve. In addition, we also found that the FDLs formed in the CH 4 N-ion-implanted Si wafer shrink with two different shrinkage rates during heat treatment.…”
mentioning
confidence: 99%
“…Previously, we have clarified the thermal stability and shrinkage behavior of FDLs formed in CH 4 N-multielement-molecular-ion-implanted epitaxial Si wafer. 35 We found that the faulted Frank dislocation loops (FDLs) formed in a CH 4 N-ion-implanted epitaxial Si wafer are thermally stable up to 1000 °C, and at temperatures above 1100 °C, most of them lose stability and finally dissolve. In addition, we also found that the FDLs formed in the CH 4 N-ion-implanted Si wafer shrink with two different shrinkage rates during heat treatment.…”
mentioning
confidence: 99%